LITERATURE REVIEW : THE INFLUENCE OF FINANCIAL TECHONOLOGY, FINANCIAL LITERACY, INVESTMENT MOTIVATION AND RISK PERCEPTION ON INVESTMENT INTEREST IN GENERATION Z IN TAMBUN SELATAN DISTRICT - Salsabila Aninda Putri; Adi Wibowo Noor Fikri; Christophorus Indra Wahyu Putra (Draf Solusi Indonesia, 2024)
This research aims to analyze the influence of financial technology, financial literacy, investment motivation, and risk perception on investment interest in generation Z in Tambun Selatan District. This research was conducted using the questionnaire distribution method as a data collection tool. The population in this study is generation Z in Tambun Selatan District with a research sample consisted of 80 respondents. The data analysis technique in this research uses Partial Least Square (PLS).